2020
DOI: 10.1021/acs.inorgchem.0c00738
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Bonding: A Key Factor Controlling the Photosubstitution of Ruthenium Complexes

Abstract: Photosubstitution reactions of ruthenium complexes with pyrazole ligands, cis-[Ru­(bpy)2(pzH)2]2+ (1a), cis-[Ru­(bpy)2(pz)­(pzH)]+ (1b), and cis-[Ru­(bpy)2(pz)2]0 (1c) (pzH = pyrazole, bpy = 2,2′-bipyridine), were investigated. Dicationic complex 1a was deprotonated to 1b using moderate base (pK a = 15.2, MeCN), while the second deprotonation to give 1c required more severe conditions (pK a = 26.9). Monocationic complex 1b possessed an N–H···N-type intramolecular hydrogen bond between the pyrazole and pyrazola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 73 publications
4
32
0
Order By: Relevance
“…The decrease of the yield is attributed to the enhancement of the photodissociation of a pyrazole ligand in 1b . We earlier reported that the photosubstitution reaction of 1b was highly dependent on the solvent, being highly accelerated in a protic solvent with a strong proton donor ability, such as water or 2,2,2-trifluoroethanol . Additionally, the relatively larger yield of 1b in D 2 O rather than in H 2 O is consistent with the deuterium effect on the photosubstitution of 1b .…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…The decrease of the yield is attributed to the enhancement of the photodissociation of a pyrazole ligand in 1b . We earlier reported that the photosubstitution reaction of 1b was highly dependent on the solvent, being highly accelerated in a protic solvent with a strong proton donor ability, such as water or 2,2,2-trifluoroethanol . Additionally, the relatively larger yield of 1b in D 2 O rather than in H 2 O is consistent with the deuterium effect on the photosubstitution of 1b .…”
Section: Resultsmentioning
confidence: 57%
“…cis -Ru­(bpy) 2 Cl 2 , cis -[Ru­(bpy) 2 (MeCN) 2 ]­(PF 6 ) 2 , cis -[Ru­(bpy) 2 (pzH) 2 ]­(PF 6 ) 2 , and 1b were prepared as previously described. The extinction coefficients and absorption maxima agreed with the reported values .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear chelate effect, explained that even if one pyridine became detached the other anchoring ring would still hold the ligand in place. 29,30 A bond elongation process, by population of the anti-bonding metalcentred d-orbital, would appear to be more significant in a photorelease mechanism for mono-dentate ligands. The full ejection of a chelate after excitation may require a secondary agent, utilising the excited state redox properties of a complex.…”
Section: Basic Photophysics and Photorelease Mechanismmentioning
confidence: 99%